Exploratory analysis of potential association between oral Haemophilus and sleep disturbances in major depressive disorder patients - Shi, Yachen; Zhao, En; Gong, Weigang; Gao, Qianqian; Li, Yang; Xi, Guangjun; Han, Yan; Weng, Hui; Wang, Feng; Geng, Feng; Zhang, Gaojia (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe current study aimed to explore the specific oral microbiota profiles in major depressive disorder (MDD) patients with sleep disturbances, and to evaluate the potential mechanisms by which oral microbiota may be implicated in MDD.MethodThirty-eight MDD patients experiencing sleep disturbances and thirty healthy controls (HCs) were included. All MDD patients underwent a 14-day antidepressive treatment regimen. Neuropsychological assessments were conducted, and 16S rRNA sequencing was used to determine the abundance of oral bacteria.ResultsOral genera Solobacterium, Granulicatella, Campylobacter, and Haemophilus showed significant changes in their relative abundances between the MDD and HC groups. Significant correlations were found between the abundance of Haemophilus and Pittsburgh Sleep Quality Index (PSQI) and 24-item Hamilton Depression Scale (HAMD-24) scores in MDD patients with sleep disturbances. In MDD patients, lower relative abundances of oral Haemophilus prior to treatment were negatively correlated with the changed rates of PSQI and HAMD-24 scores after antidepressive treatment. The glial fibrillary acidic protein as the mediator, affected the relationship between the relative abundance of oral Haemophilus and sleep disturbances in MDD patients.ConclusionOral Haemophilus dysbiosis may drive sleep disturbances in MDD patients, possibly through its impact on neuroinflammation.